Magnetic and Structural Properties of Organic Radicals Based on Thienyl- and Furyl-Substituted Nitronyl Nitroxide - Tadashi Sugano; Stephen J. Blundell; William Hayes; Hatsumi Mori (Magnetochemistry, 2021)
Magnetic properties of organic radicals based on thienyl- and furyl-substituted nitronyl nitroxide (NN) and iminonitroxide (IN) were investigated by measuring the temperature dependence of the magnetization. The magnetic behavior of 2-benzo[b]thienyl NN (2-BTHNN) is interpreted in terms of the two-magnetic-dimer model, in which one dimer exhibits ferromagnetic (FM) intermolecular interaction and the other dimer shows antiferromagnetic (AFM) interaction. The existence of two dimers in 2-BTHNN is supported by crystal structure analysis. The magnetic behaviors of 2-bithienyl NN, 4-(2′-thienyl)phenyl NN (2-THPNN), 2- and 3-furyl NN, 2-benzo[b]furyl NN, and 3-benzo[b]thienyl IN are also reported. The one-dimensional alternating AFM nature observed in 2-THPNN is consistent with its crystal structure.